Binder and application thereof in lithium battery

The adhesive made by blending amphiphilic polymer and flexible polymers solves the problem of taking into account both the mechanical strength and flexibility of the negative electrode adhesive of lithium-ion batteries, and achieves high elastic modulus, elongation of break and low The effect of swelling improves the cycling performance and structural stability of the battery.

CN119410304APending Publication Date: 2025-02-11SHENZHEN HAODYNE TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510012720.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

While improving the mechanical strength of existing lithium-ion battery negative electrode adhesives, it is difficult to take into account high flexibility and low swelling, resulting in cracking, rebound and changes in the electrode sheet processing.

Method used

The binder is made by blending amphiphilic polymer and oil-soluble flexible polymer. The amphiphilic polymer contains hydrophilic and lipophilic structural units, and the mass proportion of the flexible polymer is between 1 wt% and 40 wt%. By controlling the molecular weight and dispersion index of the polymer, the flexibility and adhesion of the binder are improved while reducing swelling.

Benefits of technology

It realizes that while ensuring the rigidity of the adhesive, it improves flexibility and toughness, and forms a bonding agent that is both rigid and flexible, overcomes the problem of cracking of the electrode sheet, inhibits the rebound of the electrode sheet, and has low swelling in the electrolyte. Characteristics to reduce battery volume changes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a binder and application thereof in a lithium battery. The binder comprises an amphiphilic polymer and an oil-soluble flexible polymer, the amphiphilic polymer comprises a hydrophilic structural unit and a lipophilic structural unit; the number-average molecular weight of the amphiphilic polymer is 1w to 500w, and the dispersity index of the amphiphilic polymer is 0.5 to 5; the number average molecular weight of the flexible polymer is 2000 to 20 w; the mass ratio of the flexible polymer is 1-40wt% by taking the total mass of the adhesive as 100%; in the amphiphilic polymer, the mass ratio of the hydrophilic structural unit to the lipophilic structural unit is (10-85): (85-10). The adhesive provided by the invention has the effects of high flexibility, low swelling property and good stability while improving the bonding mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a binder and its application in lithium batteries. Background Art

[0002] Lithium-ion batteries mainly include positive electrode, negative electrode, electrolyte, separator, casing and electrode lead structure. The positive and negative electrode sheets need to be coated with a slurry mixed with active materials, thickeners, binders and conductive agents. Among them, the negative electrode binder plays a vital role in the silicon electrode.

[0003] At present, in order to improve the performance of silicon negative electrode binders, the relevant technology, for example, a Chinese patent with publication number CN117757425A discloses a lithium ion battery negative electrode binder and its preparation method and application, which introduces small molecule tannic acid (TA), selects small molecule phthalic acid (Phthalic acid) with two carboxyl groups, and reacts with carboxymethyl cellulose (CMC) to form a new structure of lithium ion battery negative electrode binder. The patent introduces phthalic acid and carboxymethyl cellulose side chains and the abundant hydroxyl groups on the small molecule tannic acid to undergo dehydration condensation reaction to prepare a CPT binder with a cross-linked network structure. This network structure can significantly improve the mechanical properties of the binder, thereby effectively inhibiting the volume expansion of the silicon-carbon negative electrode during the charge and discharge process.

[0004] In addition, in the related art, for example, a Chinese patent with publication number CN117050679A discloses a silicon negative electrode binder with a chemical / ionic / hydrogen bond triple cross-linked network and a preparation method. The hydroxyl groups of β-CD and the hydroxyl groups on the Si surface react to form a hydrogen bond cross-linked network, and an in-situ esterification reaction occurs between β-CD, CA, ALG and the Si surface to form a chemical cross-linked network, and the carboxyl groups generated by the hydrolysis of the cross-linked ester groups react with the carboxyl groups of CA and the CuO formed by partial oxidation on the copper current collector to form a carboxylate copper complex and diffuse to the electrode to form an ionic cross-linked network, thereby forming a triple cross-linked binder with a three-dimensional network structure. β-CD is used as one of the raw materials to introduce a large number of active hydroxyl groups, promote hydrogen bond cross-linking, and enable the prepared silicon negative electrode to self-repair fractures during the cycle and maintain integrity, thereby effectively improving the cycle stability of the silicon negative electrode.

[0005] The binders in the related technologies all emphasize the role of the cross-linked network in improving the mechanical strength of the binder material. However, although the cross-linked structure improves the rigidity, it also leads to the destruction of the electrode microstructure during the subsequent rolling process of the electrode sheet, resulting in a loss of peeling force, especially in the preparation process of thick electrodes, which leads to cracking of the electrode sheet and inability to roll it up, and problems of electrode sheet cutting and shedding. In addition, although the related technologies emphasize the role of hydrogen bonds in improving the flexibility of binders, the destruction and reconstruction of hydrogen bonds give the electrode self-healing properties. However, the construction of hydrogen bonds requires that the binder has a high swelling in the electrolyte, which will cause a large rebound of the electrode, resulting in a large volume change in the battery during service, especially in the case of large-capacity cells, which will damage the cell structure and cause capacity decay. Summary of the invention

[0006] In order to improve the mechanical strength of the binder while having high flexibility and low swelling, the present application provides a binder and its application in a lithium battery.

[0007] In a first aspect, the present application provides a binder, which adopts the following technical solution: A binder comprising an amphiphilic polymer and an oil-soluble flexible polymer; The amphiphilic polymer comprises a hydrophilic structural unit and a lipophilic structural unit; The number average molecular weight of the amphiphilic polymer is 1w-500w, and the dispersity index of the amphiphilic polymer is 0.5-5; The number average molecular weight of the flexible polymer is 2000-20w; Taking the total mass of the binder as 100%, the mass proportion of the flexible polymer is 1wt%-40wt%; In the amphiphilic polymer, the mass ratio of the hydrophilic structural unit to the lipophilic structural unit is (10-85): (85-10).

[0008] By adopting the above technical scheme, the amphiphilic polymer and the flexible polymer are blended to produce a synergistic effect, which can improve the flexibility and toughness while ensuring the rigidity of the adhesive, forming a rigid and flexible adhesive. After the rolling process, it still has a strong peeling force. Its high flexibility overcomes the problem of cracking during electrode processing, and its high toughness inhibits the rebound of the electrode. It also has low swelling characteristics in the electrolyte, reducing the volume change of the battery.

[0009] The amphiphilic polymer includes a hydrophilic structural unit and a lipophilic structural unit. The presence of the hydrophilic structural unit helps to improve the hydrophilicity of the amphiphilic polymer and helps to improve the adhesion of the adhesive. The presence of the lipophilic structural unit helps to improve the lipophilicity of the amphiphilic polymer and helps to improve the compatibility with the flexible polymer. Preferably, the introduction of the amphiphilic structural unit into the amphiphilic polymer helps to increase the applicability of the adhesive, regulate the hydrophilicity and lipophilicity of the amphiphilic polymer, and inhibit the sedimentation of the amphiphilic polymer in an aqueous or oily solution, thereby helping to improve the compatibility with the flexible polymer, so that the amphiphilic polymer can synergize with the flexible polymer to improve the flexibility and adhesion of the adhesive, while having the advantage of low swelling.

[0010] In the present invention, in the above-mentioned amphiphilic polymer, the hydrophilic structural unit represents the structural unit corresponding to the hydrophilic monomer in the amphiphilic polymer obtained by polymerization with the participation of the hydrophilic monomer, and similarly, the lipophilic structural unit represents the structural unit corresponding to the lipophilic monomer in the amphiphilic polymer obtained by polymerization with the participation of the lipophilic monomer. Correspondingly, in the amphiphilic polymer, the mass ratio of the hydrophilic structural unit to the lipophilic structural unit represents the mass ratio of the hydrophilic monomer to the lipophilic monomer participating in the polymerization.

[0011] Optionally, the amphiphilic polymer is obtained by solution polymerization in an aqueous solution or an oily solution. When polymerized in the aqueous solution, the mass ratio of the hydrophilic monomer to the lipophilic monomer is (10-35):(60-85); when polymerized in the oily solution, the mass ratio of the lipophilic monomer to the hydrophilic monomer is (10-35):(60-85).

[0012] Specifically, when polymerizing in the aqueous solution, the mass fraction of the hydrophilic monomer can be 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 25 parts, 28 parts, 30 parts, 33 parts, 35 parts, etc., and the mass fraction of the lipophilic monomer can be 60 parts, 63 parts, 65 parts, 68 parts, 70 parts, 75 parts, 80 parts, 85 parts, etc.; when polymerizing in the oily solution, the mass fraction of the lipophilic monomer can be 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 25 parts, 28 parts, 30 parts, 33 parts, 35 parts, etc., and the mass fraction of the hydrophilic monomer can be 60 parts, 63 parts, 65 parts, 68 parts, 70 parts, 75 parts, 80 parts, 85 parts, etc.

[0013] By adopting the above technical scheme, more lipophilic monomers are added than hydrophilic monomers during polymerization in an aqueous solution. On the one hand, the hydrophilicity of the amphiphilic polymer can be ensured, and then when the amphiphilic polymer is blended with an oil-soluble flexible polymer, more oily functional groups are more conducive to mixing with the flexible polymer, thereby improving the stability of the polymer; more hydrophilic monomers are added than lipophilic monomers during polymerization in an oily solution, and by controlling the mass proportion of the hydrophilic monomers in the oily solution system in the present application, it is helpful to improve the polarity of the polymer itself, and the increase in polarity helps to improve the bonding force between the binder and the main material of the battery and the current collector, thereby improving the bonding effect.

[0014] Optionally, in the amphiphilic polymer, the hydrophilic structural unit is a structural unit containing one or more of -OH, -CHO, -COOH, -NH2, and -SO3H groups; the lipophilic structural unit is a structural unit containing -C n H 2n+1 , -C6H5, -NO2 group, halogenated hydrocarbon or one or more of the following structural units.

[0015] The hydrophilic structural unit is selected from one or more of a hydroxymethyl acrylate structural unit, a hydroxyethyl acrylate structural unit, a hydroxypropyl acrylate structural unit, a hydroxybutyl acrylate structural unit, a hydroxypentyl acrylate structural unit, a hydroxyhexyl acrylate structural unit, an acrylamide hydroxymethyl ester structural unit, an acrylamide hydroxyethyl ester structural unit, an acrylamide hydroxypropyl ester structural unit, a 3-methacryloyl dopamine structural unit, a 2-hydroxy-3-phenoxypropyl acrylate structural unit, an acrylic acid structural unit, an itaconic acid structural unit, a maleic acid structural unit, a cinnamic acid structural unit, a methacryloyloxyethyl succinate structural unit, a 2-methacryloyloxyethyl phthalate structural unit, a hydroxyethyl dimethacrylate structural unit of phthalic anhydride, an acrylamide structural unit, a dimethylacrylamide structural unit, a methacrylamide structural unit, a caprolactam structural unit, a 2-acrylamide-2-methylpropanesulfonic acid structural unit, a vinylsulfonic acid structural unit, and a [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide structural unit.

[0016] The lipophilic structural unit is selected from one or more of a methyl (meth)acrylate structural unit, an ethyl (meth)acrylate structural unit, a propyl (meth)acrylate structural unit, a butyl (meth)acrylate structural unit, a pentyl (meth)acrylate structural unit, a hexyl (meth)acrylate structural unit, a laurate (meth)acrylate structural unit, a styrene structural unit, a benzyl methacrylate structural unit, a perfluorobutylethyl acrylate structural unit, a 2-perfluorobutylethylene structural unit, a 2-perfluorooctylethylene structural unit, a 2-perfluorohexylethylene structural unit, a hexafluorobutyl acrylate structural unit, a trifluoroethyl acrylate structural unit, a 2-perfluoroalkylethyl methacrylate structural unit, an octafluoropentyl acrylate structural unit, a nitroethylene structural unit, and a gem-dinitropropyl acrylate structural unit.

[0017] Taking the total mass of the binder as 100%, the mass proportion of the flexible polymer is 1wt%-40wt%; Preferably, when the flexible polymer is blended with the amphiphilic polymer obtained by polymerization in an aqueous solution to form a binder, the mass proportion of the flexible polymer is 1wt%-10wt%; when the flexible polymer is blended with the amphiphilic polymer obtained by polymerization in an oily solution to form a binder, the mass proportion of the flexible polymer is 1wt%-40wt%.

[0018] Specifically, when the amphiphilic polymer obtained by polymerization in the aqueous solution is blended with the flexible polymer, the mass proportion of the flexible polymer in the total mass of the binder (i.e., the amphiphilic polymer and the flexible polymer) can be 1 wt%, 3 wt%, 5 wt%, 8 wt%, 10 wt%, etc.; when the amphiphilic polymer obtained by polymerization in the oily solution is blended with the flexible polymer, the mass proportion of the flexible polymer in the total mass of the binder (i.e., the amphiphilic polymer and the flexible polymer) can be 1 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, etc.

[0019] By adopting the above technical scheme, when the flexible polymer is blended with the amphiphilic polymer obtained by polymerization in an aqueous solution, the mass proportion of the flexible polymer is 1%-10%, which can reduce the occurrence of sedimentation and precipitation; when the flexible polymer is blended with the amphiphilic polymer obtained by polymerization in an oily solution, the mass proportion of the flexible polymer is 1%-40%, which can ensure that the occurrence of precipitation and sedimentation is reduced while having a better blending effect, thereby improving the adhesion and stability of the adhesive.

[0020] Optionally, the amphiphilic polymer further comprises an amphiphilic structural unit, and the mass proportion of the amphiphilic structural unit in the amphiphilic polymer is 4wt%-6wt%. The amphiphilic structural unit is selected from one or more of (4-(2-(acryloyloxy)ethoxy)benzylidenetriethylammonium bromide and polyethylene glycol methacrylate.

[0021] The flexible polymer is one of R-terminated polydimethylsiloxane, hydroxyl-terminated polyfluorosilicone rubber, amino silicone rubber, and amino polyether, wherein the R group is one of hydroxyl, carboxyl, or amino.

[0022] By adopting the above technical solution, the aqueous solution is deionized water, and the oily solution is NMP, DMF, DMI, chloroform, DMSO, toluene or cycloalkane.

[0023] In the present invention, the elastic modulus of the adhesive can reach 300-2000MPa, and has excellent structural stability. At the same time, the adhesive has good flexibility, and the elongation at break is 10%-500%. The test method of the elastic modulus and elongation at break of the adhesive is well known to those skilled in the art. For example, the adhesive is placed in a PTFE mold with a length*width*thickness of 10cm*1cm*0.01cm, placed in a cool and dry place at room temperature for 2 to 3 days, and then transferred to a 60°C blast oven for drying for 8 hours to form a film, which is tested in a universal stretching machine.

[0024] Test conditions: Test speed: 200mm / min, gauge length: 25.00mm, test temperature 25℃, test humidity: 49%.

[0025] At the same time, the swelling degree of the binder is low, only 0.1-1%. The test method of the swelling degree of the binder is also well known to those skilled in the art, for example: bake the sample at 120°C for 2 hours, put the sample into a test bottle, pour in the electrolyte (composition EC:EMC:DEC=3:2:5, LiPF6 concentration 1mol / L), the electrolyte is not less than 15 times the volume of the test sample, and put the test bottle into a 70°C oven for continuous heating for 72 hours.

[0026] Swelling degree = mass of sample after immersion / mass of sample before immersion When the above binder is used in a battery, it is beneficial to maintain the stability of the battery core structure.

[0027] Preferably, the glass transition temperature Tg of the binder is 70-120°C.

[0028] In the present invention, the aforementioned amphiphilic polymer can be prepared by conventional methods in the field of chemical synthesis, for example, a hydrophilic monomer, a lipophilic monomer and an amphiphilic monomer are subjected to solution polymerization in an oily solvent NMP, an initiator is added, and the initiator is azobisisobutyronitrile, and the reaction is carried out at 60-80° C. for 4-10 hours to obtain an amphiphilic polymer. As known to those skilled in the art of chemical synthesis, the molecular weight and molecular weight dispersity index PDI of the amphiphilic polymer can be controlled by controlling the monomer addition rate and the reaction temperature.

[0029] The aforementioned flexible polymer can be directly obtained from commercial sources. As known to those skilled in the art, when purchasing, a polymer with a desired molecular weight can be directly selected.

[0030] The binder provided by the present invention can be prepared by a method commonly used in the field of chemical synthesis, and the preparation method thereof is as follows: 1. The hydrophilic monomer, the lipophilic monomer and the amphiphilic monomer are solution polymerized in the oily solvent NMP, an initiator is added, and the initiator is azobisisobutyronitrile. The reaction is carried out at 60-80° C. for 4-10 hours to obtain an amphiphilic polymer.

[0031] 2. The amphiphilic polymer prepared above is blended with the flexible polymer in a weight ratio of 3:2 to obtain a binder.

[0032] In a second aspect, the present application provides an application of a binder in a lithium-ion battery. For example, the binder can be used to prepare a pole piece of a lithium-ion battery. Furthermore, the pole piece can be used to prepare a lithium-ion battery.

[0033] The method for preparing a lithium ion battery using the binder provided by the present invention is conventional, for example, comprising the following steps: 1. The binder, lithium nickel cobalt manganese ternary positive electrode material (NCM), and conductive agent conductive carbon black (super P) were blended in a mass ratio of 3:95:2 to obtain a blended powder, and the powder was blended with N-methylpyrrolidone (NMP) in a ratio of 1:20 to obtain a slurry.

[0034] 2. Coat the slurry on aluminum foil with a coating thickness of 300μm, dry it at 120℃, and roll it by roller-to-roll method. The surface density of the pole piece is 120g / m 2 , compacted density is 1.6g / cm 3 , cut into positive electrode pieces of fixed proportions.

[0035] 3. After assembling the positive electrode sheet, separator, and graphite negative electrode sheet stack into a dry battery cell, inject liquid to obtain a lithium battery. The electrolyte is 1 mole of lithium hexafluorophosphate (LiPF6) dissolved in a solvent of ethylene carbonate (EC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC) in a mass ratio of 1:2:1, that is, 1M LiPF6+ EC / DEC / EMC (1:2:1 wt%).

[0036] In summary, this application has the following beneficial effects: 1. The binder provided in the present application includes an amphiphilic polymer with a specific molecular weight and dispersibility index, and a flexible polymer with a specific molecular weight, wherein the amphiphilic polymer contains a specific content of hydrophilic structural units and lipophilic structural units. Under the above system, the lipophilic structural unit not only increases the lipophilicity of the polymer, but also increases the compatibility with the flexible polymer; the hydrophilic structural unit increases the hydrophilicity of the polymer and improves the adhesion of the polymer. The above design expands the versatility of the binder and is compatible with aqueous / oily solvents. The binder structure improves flexibility without sacrificing material rigidity, forming a rigid and flexible solvent-based binder with a high elastic modulus and a high elongation at break, which solves the problem of processing cracking of high-rigidity binder materials and improves the peel strength of the pole piece; at the same time, it has a low swelling characteristic in the electrolyte, which is beneficial to suppress the rebound of the pole piece and reduce the volume change of the battery.

[0037] 2. In the aqueous solution system, the amphiphilic polymer has more lipophilic structural units than hydrophilic structural units, which can ensure the hydrophilicity of the amphiphilic polymer on the one hand, and more lipophilic structural units are more conducive to the mixing of the amphiphilic polymer and the flexible polymer, thereby improving the stability of the polymer. In the oily solution system, the amphiphilic polymer has more hydrophilic structural units than lipophilic structural units, which helps to improve the polarity of the amphiphilic polymer itself. The increase in polarity helps to improve the bonding force between the binder and the main battery material and the current collector, thereby improving the bonding effect. DETAILED DESCRIPTION

[0038] The experimental methods in the following examples of the present invention that do not specify specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various commonly used chemical reagents used in the examples are all commercially available products. The following sources of raw materials are disclosed only for the purpose of disclosure and should not limit the scope of protection.

[0039] Source of raw materials:

[0040] Acrylic acid (CAS No. 79-10-7); hydroxyethyl acrylamide (CAS No. 7646-67-5); methyl methacrylate (CAS No. 80-62-6); perfluorobutylethyl acrylate (CAS No. 52591-27-2); azobisisobutyronitrile (CAS No. 78-67-1); 3-methacryloyl dopamine (CAS No. 471915-89-6); 2-hydroxy-3-phenoxypropyl acrylate (CAS No. 169 69-10-1); methacryloyloxyethyl succinate (CAS No.: 20882-04-6); 2-methacryloyloxyethyl phthalate (CAS No.: 27697-00-3); hydroxyethyl dimethacrylate (CAS No.: 83418-60-4); 2-acrylamide-2-methylpropanesulfonic acid (CAS No.: 15214-89-8); vinyl sulfonic acid (CAS No.: 1184-84-5); [2-(methacryloyloxyethyl) phthalate [Acyloxy)ethyl] dimethyl-(3-sulfonic acid propyl) ammonium hydroxide (CAS No.: 3637-26-1); benzyl methacrylate (CAS No.: 2495-37-6); perfluorobutyl ethyl acrylate (CAS No.: 52591-27-2), 2-perfluorobutylethylene (CAS No.: 19430-93-4), 2-perfluorooctylethylene (CAS No.: 21652-58-4), 2-perfluorohexylethylene (CAS No.: 25291- 17-2), hexafluorobutyl acrylate (CAS No.: 54052-90-3), trifluoroethyl acrylate (CAS No.: 407-47-6), 2-perfluoroalkylethyl methacrylate (CAS No.: 65530-66-7), octafluoropentyl acrylate (CAS No.: 376-84-1); nitroethylene (CAS No.: 3638-64-0); gem-dinitropropyl acrylate (DNPA); azobisisobutyronitrile (CAS: 78-67-1).

[0041] 4-(2-(acryloyloxy)ethoxy)benzylidene triethylammonium bromide is prepared by an existing synthetic route, and its preparation method comprises the following steps: 1. 20g p-cresol and 7.4g sodium hydroxide were mixed and dissolved in 70mL ethanol. After stirring at 70°C for 30 minutes, an ethanol solution of 2-chloroethanol (14.9g) was added dropwise to the mixed solution. After the addition was complete, the mixed system refluxed for 4 hours. Then the solvent ethanol in the concentrated reaction system was diluted with ethyl acetate, and the organic phase was washed alternately with distilled water and saturated sodium chloride solution. The organic phase was then dried over anhydrous magnesium sulfate, the solvent was spin-dried, and the mixed product was separated by chromatography, and the eluent was dichloromethane. Finally, a light yellow oily liquid I was obtained.

[0042] 2. Dissolve 0.2 mol of the above product I and 0.24 mol of triethylamine in anhydrous dichloromethane, and add a dichloromethane solution of 0.29 mol of acryloyl chloride dropwise at 0-5°C. After the addition, stir at room temperature for 12 hours. After the reaction is completed, filter to remove the solid triethylamine hydrochloride produced by the reaction, wash the filtrate with distilled water and saturated sodium bicarbonate solution, and dry the organic phase with anhydrous magnesium sulfate. Spin dry the solvent to obtain a yellow oily liquid product II.

[0043] 3. Dissolve 10g of the above product II in 80mL of anhydrous carbon tetrachloride, then add 10.4g of bromosuccinimide and 0.16g of benzoyl peroxide, and stir the mixture under reflux for 5-6 hours. When the reaction just begins, bromosuccinimide is insoluble in carbon tetrachloride and precipitates at the bottom of the reaction vessel. After the reaction is complete, the succinimide insoluble in carbon tetrachloride floats on the surface of the solution. Filter to remove solid succinimide, and spin-dry the solvent in the filtrate to obtain an orange-yellow oily liquid III.

[0044] 4. Dissolve the above reaction product III (1 mol) in anhydrous tetrahydrofuran, and add a tetrahydrofuran solution of triethylamine (1.05 mol) dropwise at room temperature. Stir the mixture at room temperature for 24 hours to produce a yellow solid precipitate insoluble in tetrahydrofuran. Wash the solid product with anhydrous ether and dry it in vacuo at 30°C to obtain a cationic polymerizable hydrotropy compound 4-(2-(acryloyloxy)ethoxy)benzylidenetriethylammonium bromide (AEBA).

[0045] Example Examples 1.1-1.3 (Prepared in Oily Solution) A binder comprising the following preparation steps: S1. The hydrophilic monomers acrylic acid, acrylamide hydroxyethyl ester, the lipophilic monomers methyl methacrylate, perfluorobutyl ethyl acrylate and the amphiphilic monomer 4-(2-(acryloyloxy)ethoxy)benzylidenetriethylammonium bromide are solution polymerized in an oily solvent NMP, an initiator is added, and the initiator is azobisisobutyronitrile. The reaction is carried out at 70°C for 8 hours to obtain an amphiphilic polymer.

[0046] S2. The amphiphilic polymer prepared in S1 is blended with a flexible polymer in a weight ratio of 3:2 (i.e., the mass proportion of the flexible polymer is 40%), wherein the flexible polymer is amino-terminated polydimethylsiloxane (molecular weight is 3000), to obtain a binder.

[0047] The preparation parameters of the binders of Examples 1.1-1.3 are shown in Table 1.

[0048] Table 1 Preparation parameters of the binders of Examples 1.1-1.3

[0049] As can be seen from Table 1, there is no significant substantial difference between the adhesives prepared in Examples 1.1-1.3, and Example 1.2 is a preferred example.

[0050] Examples 2.1-2.3 (Prepared in aqueous solution) A binder comprising the following preparation steps: S1. The hydrophilic monomers maleic acid and acrylamide, the lipophilic monomers ethyl acrylate and styrene, and the amphiphilic monomer 4-(2-(acryloyloxy)ethoxy)benzylidenetriethylammonium bromide are subjected to solution polymerization in an aqueous solvent, wherein the aqueous solution is deionized water, and an initiator is added, wherein the initiator is azobisisobutyronitrile, and the reaction is carried out at 70°C for 8 hours to obtain an amphiphilic polymer.

[0051] S2. The amphiphilic polymer prepared in S1 is blended with a flexible polymer in a weight ratio of 90:10, that is, the mass proportion of the flexible polymer is 10%, and the flexible polymer is amino-terminated polydimethylsiloxane (molecular weight is 2000), to obtain a binder.

[0052] The preparation parameters of the binders of Examples 2.1-2.3 are shown in Table 2.

[0053] Table 2 Preparation parameters of the binders of Examples 2.1-2.3

[0054] As can be seen from Table 2, there is no significant substantial difference between the adhesives prepared in Examples 2.1-2.3, and Example 2.2 is a preferred example.

[0055] Example 3

[0056] A binder, which is different from Example 1.2 in that the mass proportion of the lipophilic structural unit is 60%, the mass proportion of the amphiphilic structural unit is 5%, and the mass proportion of the hydrophilic structural unit is 35%.

[0057] Example 4

[0058] A binder, which is different from Example 2.2 in that the mass proportion of the hydrophilic structural unit is 60%, the mass proportion of the amphiphilic structural unit is 5%, and the mass proportion of the lipophilic structural unit is 35%.

[0059] Example 5

[0060] A binder, which is different from Example 1.2 in that the hydrophilic monomer is replaced by hydroxymethyl acrylate and itaconic acid in equal amounts, and the lipophilic monomer is replaced by methyl acrylate and 2-perfluorobutylethylene in equal amounts for solution polymerization, and the remaining steps are the same.

[0061] Example 6

[0062] A binder, which is different from Example 1.2 in that the hydrophilic monomer is replaced by hydroxyethyl acrylate and methacrylamide in equal amounts, and the lipophilic monomer is replaced by propyl acrylate and nitroethylene in equal amounts for solution polymerization, and the remaining steps are the same.

[0063] Example 7

[0064] A binder, which is different from Example 1.2 in that the hydrophilic monomer is replaced by hydroxypropyl acrylate and vinyl sulfonic acid in equal amounts, and the lipophilic monomer is replaced by butyl acrylate and styrene in equal amounts for solution polymerization, and the remaining steps are the same.

[0065] Comparative Example

[0066] Comparative Example 1 A binder, which is different from Example 1.2 in that the amount of the hydrophilic monomer used is 0 kg.

[0067] Comparative Example 2 A binder, which is different from Example 1.2 in that the amount of the lipophilic monomer used is 0 kg.

[0068] Comparative Example 3 A binder, which is different from Example 1.2 in that the amount of the amphiphilic monomer used is 0 kg.

[0069] Comparative Example 4 A binder, which is different from Example 1.2 in that the amphiphilic polymer is prepared by reacting at 60° C. for 14 hours, and the number average molecular weight of the prepared amphiphilic polymer is 600W.

[0070] Comparative Example 5 A binder, which is different from Example 1.2 in that the amphiphilic polymer and the flexible polymer are blended in a mass ratio of 2:3, that is, the mass proportion of the flexible polymer is 60%.

[0071] Comparative Example 6 A binder, which is different from Example 2.2 in that the amphiphilic polymer and the flexible polymer are blended in a mass ratio of 10:90, that is, the mass proportion of the flexible polymer is 90%.

[0072] Application Examples

[0073] Application Example 1 An application of a binder in a lithium ion battery comprises the following steps: A1. The binder prepared in Example 1.2, the lithium nickel cobalt manganese ternary positive electrode material (NCM), and the conductive agent conductive carbon black (super P) are blended in a mass ratio of 3:95:2 to obtain a blended powder, and the powder is blended with N-methylpyrrolidone (NMP) in a mass ratio of 1:20 to obtain a slurry.

[0074] A2. The slurry is coated on aluminum foil with a coating thickness of 300 μm, dried at 120°C, and rolled by roll-to-roll method. The surface density of the pole piece is 120 g / m 2 , compacted density is 1.6g / cm 3 , and then cut into positive electrode sheets of fixed size after rolling.

[0075] A3. After assembling the positive electrode sheet and the graphite negative electrode sheet stack into a dry battery cell, the electrolyte is injected to obtain a lithium battery. The electrolyte is 1 mole of lithium hexafluorophosphate (LiPF6) dissolved in a mixed solvent of ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) in a mass ratio of 1:2:1, that is, 1M LiPF6+ EC / DEC / EMC (1:2:1 wt%).

[0076] Application Example 2 An application of a binder in a lithium-ion battery is different from Application Example 1 in that the binder in A1 is prepared by Example 2.2, and the binder is blended with a lithium nickel cobalt manganese ternary positive electrode material (NCM) and a conductive agent conductive carbon black (super P) in a mass ratio of 2:97:1; the drying temperature in A2 is 80°C, and the rest are the same.

[0077] Application Example 3-7 An application of a binder in a lithium ion battery is different from Application Example 1 in that the binder is a binder prepared in Example 3 to Example 7 in sequence.

[0078] Comparative Application Examples 1-6 An application of a binder in a lithium ion battery is different from Application Example 1 in that the binder is the binder prepared in Comparative Examples 1 to 6 in sequence.

[0079] Comparative Application Example 7 An application of a binder in a lithium ion battery comprises the following steps: A1. Blend a polyacrylic acid PAA binder (molecular weight of 100-300w), a silicon negative electrode, and a conductive agent super P in a mass ratio of 2:97:1 to obtain a blended powder, and blend the powder with deionized water in a ratio of 1:20 to obtain a slurry.

[0080] A2. Coat the slurry on copper foil with a coating thickness of 300 μm. After drying at 80°C and rolling by roll-to-roll method, the electrode surface density is 120 g / m 2 , compacted density is 1.6g / cm 3 , cut into negative electrode sheets of fixed proportions.

[0081] A3. After the negative electrode sheet and the NCM positive electrode sheet are stacked and assembled into a dry battery cell, the electrolyte is injected to obtain a lithium battery. The electrolyte is 1 mole of lithium hexafluorophosphate (LiPF6) dissolved in a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a mass ratio of 1:1, that is, 1M LiPF6 + EC / DEC (1:1 wt%).

[0082] Comparative Application Example 8 An application of a binder in a lithium ion battery comprises the following steps: A1. Blend polyacrylamide PVDF binder (molecular weight 100-300w), ternary positive electrode NCM, and conductive agent super P in a mass ratio of 3:95:2 to obtain a blended powder, and blend the powder with NMP in a ratio of 1:20 to obtain a slurry. A2. The slurry is coated on aluminum foil with a coating thickness of 300 μm. After drying at 120°C, it is rolled by roll-to-roll method and then cut into negative electrode sheets of fixed size.

[0083] A3. After assembling the negative electrode sheet and the NCM positive electrode sheet stack into a dry cell, the lithium battery is injected with liquid. The electrolyte is 1 mole of lithium hexafluorophosphate (LiPF6) dissolved in a mixed solvent of ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) in a mass ratio of 1:2:1, that is, 1M LiPF6 + EC / DEC / EMC (1:2:1 wt%).

[0084] Performance testing

[0085] 1. Adhesive stability test The adhesives of Example 1.2, Example 2.2, Examples 3-7 and Comparative Examples 1-6 were tested, and the test method was as follows: Take 100 ml of adhesive with an initial solid content of s, pour it into a cylindrical container with a diameter of 2 cm, and seal it. After storing it at 60°C for 72 hours, take it out and cool it to room temperature. Then test the solid content s1 of the top adhesive and the solid content s2 of the bottom adhesive. If |s1-s2| / s≤1%, the adhesive has not been stratified / sedimented.

[0086] 2. Peel strength test The corresponding use cases 1-7 and comparative application examples 1-8 are tested in the following way: The adhesive was applied to the electrode, attached to the electrode with 3M double-sided tape, rolled with a pressure roller, and then tested for peeling force with a universal tensile machine fixture. The peeling force test was performed at a test speed of 50 mm / min. The test environment was: 25°C, RH: 40-50%.

[0087] 3. Elastic modulus and elongation at break test Corresponding test cases 1-7 and comparative application cases 1-8 are tested.

[0088] Among them, the test methods for elastic modulus and elongation at break are as follows: Sample preparation method: Place the adhesive into a PTFE mold with a length * width * thickness of 10cm * 1cm * 0.01cm, place it in a cool and dry place at room temperature for 2 to 3 days, then transfer it to a 60℃ forced air oven and dry it for 8 hours to form a film, which is then tested in a universal stretching machine.

[0089] Test conditions: Test speed: 200mm / min, gauge length: 25.00mm, test temperature 25℃, test humidity: 49%.

[0090] 4. Swelling test The corresponding use cases 1-7 and comparative application examples 1-8 are tested in the following way: Bake the sample at 120℃ for 2h, put the sample into the test bottle, pour in the electrolyte (composition EC:EMC:DEC=3:2:5, LiPF6 concentration 1mol / L), the electrolyte volume should be no less than 15 times the volume of the test sample, and put the test bottle into a 70℃ oven for continuous heating for 72h. Swelling degree = sample mass after immersion / sample mass before immersion The test results are shown in Table 3 and Table 4. Table 3 Test results of Example 1.2, Example 2.2, Examples 3-7 and Comparative Examples 1-6

[0091] Table 4 Test results of application examples 1-7 and comparative application examples 1-8

[0092] It can be seen from the above test results that the binder provided by the present invention has excellent elastic modulus and elongation at break, stable structure and good flexibility. At the same time, the binder has high peel strength and very low swelling degree, which can effectively improve the cycle performance of the battery.

[0093] Combining the test results of Example 1.2, Application Example 1 and Example 3, Application Example 3 and Table 3-Table 4, it can be seen that the binder test of Example 1.2 is better than that of Example 3. The reason may be that more hydrophilic monomers are added than lipophilic monomers during polymerization in an oily solution, and by controlling the weight ratio of lipophilic monomers to hydrophilic monomers in the oily solution system to (10-35): (60-85), it helps to improve the polarity of the polymer itself. The increase in polarity helps to improve the bonding force between the binder and the main material of the battery and the current collector, thereby improving the bonding effect.

[0094] Combining Example 2.2, Application Example 2 and Example 4, Application Example 4 and the test results of Tables 3 and 4, it can be seen that Example 2.2 is better than the binder of Example 4. The reason may be: more lipophilic monomers than hydrophilic monomers are added during polymerization in an aqueous solution, which can ensure the hydrophilicity of the amphiphilic polymer. Then, when the amphiphilic polymer is blended with an oil-soluble flexible polymer, more oily functional groups are more conducive to mixing with the flexible polymer, thereby improving the stability of the polymer, thereby ensuring that the binder has a high elastic modulus, elongation at break, peel strength and low swelling.

[0095] It can be seen from Example 1.2 and Comparative Examples 1-4, Application Example 1 and Comparative Application Examples 1-4 and Tables 3-4 that Example 1.2 is better than Comparative Examples 1-4. The reason for this is that: the amphiphilic polymer used in the present application includes a hydrophilic structural unit and a lipophilic structural unit. The presence of the hydrophilic structural unit helps to improve the hydrophilicity of the amphiphilic polymer while helping to improve the adhesion of the adhesive. The presence of the lipophilic structural unit helps to improve the lipophilicity of the amphiphilic polymer while helping to improve the compatibility with the flexible polymer; the introduction of amphiphilic structural units into the amphiphilic polymer helps to increase the applicability of the adhesive, regulate the hydrophilicity and lipophilicity of the amphiphilic polymer, and inhibit the sedimentation of the amphiphilic polymer in an aqueous or oily solution, thereby helping to improve the compatibility with the flexible polymer, so that the amphiphilic polymer can synergize with the flexible polymer to improve the flexibility and adhesion of the adhesive, and at the same time has the advantage of low swelling.

[0096] Combining Application Example 1 and Comparative Application Examples 7-8 and the test results in Table 4, it can be seen that Application Example 1 is better than Comparative Application Examples 7-8. The reason for this is that the amphiphilic polymer and the flexible polymer blended in this application produce a synergistic effect, which can improve the flexibility and toughness while ensuring the rigidity of the adhesive, forming a rigid and flexible adhesive. After the rolling process, it still has a strong peeling force. Its high flexibility overcomes the problem of cracking during electrode processing, and its high toughness inhibits the rebound of the electrode. It has low swelling characteristics in the electrolyte, reducing the volume change of the battery.

[0097] It can be seen from Example 1, Application Example 1 and Comparative Examples 5-6, and Comparative Application Examples 5-6 and Tables 3 and 4 that the test results of Example 1 and Application Example 1 are better than those of Comparative Examples 5-6 and Comparative Application Examples 5-6. The reason may be that when the mass proportion of the flexible polymer and the amphiphilic polymer obtained by polymerization in the aqueous solution is in the range of 1%-10% when blended, the sedimentation and precipitation can be reduced; when the mass proportion of the flexible polymer and the amphiphilic polymer obtained by polymerization in the oily solution is in the range of 1%-40% when blended, it can ensure that the precipitation and sedimentation are reduced, and at the same time, it can have a better blending effect, thereby improving the adhesion and stability of the binder.

[0098] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A binder, characterized in that: Includes amphiphilic polymers and oil-soluble flexible polymers; The amphiphilic polymer comprises a hydrophilic structural unit and a lipophilic structural unit; The number average molecular weight of the amphiphilic polymer is 1w-500w, and the dispersity index of the amphiphilic polymer is 0.5-5; The number average molecular weight of the flexible polymer is 2000-20w; Taking the total mass of the binder as 100%, the mass proportion of the flexible polymer is 1wt%-40wt%; In the amphiphilic polymer, the mass ratio of the hydrophilic structural unit to the lipophilic structural unit is (10-85): (85-10).

2. The adhesive according to claim 1, characterized in that: The elastic modulus of the binder is 300-2000 MPa, and the elongation at break is 10%-500%.

3. The adhesive according to claim 1, characterized in that: The swelling degree of the binder is 0.1-1%.

4. The adhesive according to claim 1, characterized in that: The glass transition temperature Tg of the binder is 70-120°C.

5. The adhesive according to any one of claims 1 to 4, characterized in that: In the amphiphilic polymer, the hydrophilic structural unit is a structural unit containing one or more of -OH, -CHO, -COOH, -NH2, and -SO3H groups; the lipophilic structural unit is a structural unit containing -C n H 2n+1 , -C6H5, -NO2 group, halogenated hydrocarbon or one or more of the following structural units.

6. The adhesive according to claim 5, characterized in that: The hydrophilic structural unit is selected from one or more of a hydroxymethyl acrylate structural unit, a hydroxyethyl acrylate structural unit, a hydroxypropyl acrylate structural unit, a hydroxybutyl acrylate structural unit, a hydroxypentyl acrylate structural unit, a hydroxyhexyl acrylate structural unit, an acrylamide hydroxymethyl ester structural unit, an acrylamide hydroxyethyl ester structural unit, an acrylamide hydroxypropyl ester structural unit, a 3-methacryloyl dopamine structural unit, a 2-hydroxy-3-phenoxypropyl acrylate structural unit, an acrylic acid structural unit, an itaconic acid structural unit, a maleic acid structural unit, a cinnamic acid structural unit, a methacryloxyethyl succinate structural unit, a 2-methacryloyloxyethyl phthalate structural unit, a hydroxyethyl pyrophthalate dimethacrylate structural unit, an acrylamide structural unit, a dimethylacrylamide structural unit, a methacrylamide structural unit, a caprolactam structural unit, a 2-acrylamide-2-methylpropanesulfonic acid structural unit, a vinylsulfonic acid structural unit, and a [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide structural unit; The lipophilic structural unit is selected from one or more of a methyl (meth)acrylate structural unit, an ethyl (meth)acrylate structural unit, a propyl (meth)acrylate structural unit, a butyl (meth)acrylate structural unit, a pentyl (meth)acrylate structural unit, a hexyl (meth)acrylate structural unit, a laurate (meth)acrylate structural unit, a styrene structural unit, a benzyl methacrylate structural unit, a perfluorobutylethyl acrylate structural unit, a 2-perfluorobutylethylene structural unit, a 2-perfluorooctylethylene structural unit, a 2-perfluorohexylethylene structural unit, a hexafluorobutyl acrylate structural unit, a trifluoroethyl acrylate structural unit, a 2-perfluoroalkylethyl methacrylate structural unit, an octafluoropentyl acrylate structural unit, a nitroethylene structural unit, and a gem-dinitropropyl acrylate structural unit.

7. The adhesive according to any one of claims 1 to 4, characterized in that: The amphiphilic polymer further contains an amphiphilic structural unit, and the mass proportion of the amphiphilic structural unit in the amphiphilic polymer is 4wt%-6wt%.

8. The adhesive according to claim 7, characterized in that: The amphiphilic structural unit is selected from one or more of (4-(2-(acryloyloxy)ethoxy)benzylidenetriethylammonium bromide and polyethylene glycol methacrylate.

9. The adhesive according to claim 1, characterized in that: The flexible polymer is one of R-terminated polydimethylsiloxane, hydroxyl-terminated polyfluorosilicone rubber, amino silicone rubber, and amino polyether, wherein the R group is one of hydroxyl, carboxyl, or amino.

10. Use of the binder according to any one of claims 1 to 9 in a lithium ion battery.

Citation Information

Patent Citations

  • Silicon negative electrode binder with chemical / ionic / hydrogen bond triple cross-linked network and preparation method of silicon negative electrode binder

    CN117050679A

  • Lithium ion battery negative electrode binder and preparation method and application thereof

    CN117757425A

  • Hydrophobic association polymer with cation surface active monomer and synthesis method thereof

    CN101724125A

  • Battery binder, lithium ion battery negative electrode plate, and lithium ion battery

    CN111500228A

  • Water-based binder for lithium ion battery diaphragm

    CN112920747A